Role of P-selectin, hemopexin, lactoferrin, iron and ferritin in patients with giardiasis and amoebiasis: a narrative review - Saleem K. Al-Hadraawy; Ali H. Abood; Rahman S. Zabibah; Ameer A. Imarah; Abbas F. Almulla; Ali Abbas Abo Algon (Russian Open Medical Journal)
The most frequent intestinal parasites that cause severe disorders in humans are Giardia lamblia and Entamoeba histolytica, which alter serum concentrations of deferent markers due to virulence factors and pathogenicity. A large number of people with infection are asymptomatic, and they can go for up to a year without showing any signs or symptoms. Additionally, due to prolonged diarrhoea but not acute diarrhoea, these parasites can cause malnutrition, weight loss, growth delay, and possibly low cognitive development. The aim of this study is to look at how giardiasis and amoebiasis affect the levels of certain biomarkers in the blood.